Hypothyroidism is a causal determinant of age-related cataract risk in European population: a Mendelian randomization study - Liu, Shu; Sun, Qi; Gu, Qingwei; Bao, Yujie; Wang, Wei; Qin, Xiaodong; Yuan, Xinran (Frontiers in Endocrinology, 2024)
Objective: To determine whether there is a causal relationship between thyroid dysfunction and the risk of age-related cataract (ARC) in the European population. Design: A two-sample Mendelian randomization (MR) study. Methods: Hypothyroidism, hyperthyroidism, free thyroxine (fT4), and thyrotropin (TSH) were selected as exposures. The single nucleotide polymorphisms (SNP) of hypothyroidism and hyperthyroidism were obtained from the genome-wide association studies (GWAS) of the IEU database, including 337,159 subjects. Data for fT4 and TSH (72,167 subjects) were extracted from the ThyroidOmics Consortium. ARC was used as the outcome. The SNPs associated with ARC were selected from a GWAS of 216,362 individuals in the FinnGen database. The main method used was the inverse variance-weighted method, together with four complementary methods. Sensitivity analyses were performed using Cochran's Q test, MR-PRESSO, MR-Egger regression and leave-one-out test. MR pleiotropy was used to test for pleiotropy. MR Steiger test was used to test for the directionality. Results: Two-sample MR analysis revealed a positive association between genetically predicted hypothyroidism and risk of ARC (OR = 2.501, 95% CI: 1.325-4.720; P = 0.004). Hyperthyroidism, circulating fT4 and TSH levels did not have a significant causal effect on ARC (P > 0.05). The results were robust and reliable, and no horizontal pleiotropy was found after sensitivity analyses. In the MR Steiger test, we found no reverse causal effects of hypothyroidism on the ARC (P <0.001). Conclusions: Our study provides strong evidence that hypothyroidism is a causal determinant of ARC risk.